Hospital-related, maternal, and fetal risk factors for neonatal asphyxia and moderate or severe hypoxic-ischemic encephalopathy: a retrospective cohort study. (3rd May 2021) - Wood, Stephen; Crawford, Susan; Hicks, Matt; Mohammad, Khorshid
Abstract: Aim: A previous large US study had documented an increased risk of asphyxia in small volume and rural hospitals. Our objective was to evaluate this in all hospitals in Alberta, a Canadian province. Methods: Retrospective cohort study of all singleton births ≥ 35-week gestation, in Alberta, from 2002–16 recorded in a perinatal database. Asphyxia was defined as intrapartum stillbirth or neonatal death from asphyxia or Neonatal Intensive Care Unit admission and at least two of the following: a. Apgar score of ≤ 5 at 10 minutes; b. mechanical ventilation or chest compressions for resuscitation within 10 minutes; c. cord pH < 7.00 (venous or arterial), or arterial base excess ≥ 12 at birth. Urban hospitals were defined as those serving a population of ≥ 50 000. Hospital volume was categorized by the following: urban: < 1200, 1200–2399, 2400–3600, > 3600 annual births and Rural: < 50, 50–599, 600–1699 annual births. Data on moderate–severe neonatal hypoxic-ischemic encephalopathy was also obtained from two provincial asphyxia databases for 2010–2016. Results: The overall rate of neonatal asphyxia was 2.28 per 1000 births for the study period and was 2.5/1000 in the urban hospitals and 1.35/1000 in the rural hospitals, OR: 1.86 95% CI (1.58, 2.19). The rate of moderate or severe neonatal hypoxic-ischemic encephalopathy was 0.9/1000 and was not associated with urban hospital birth; OR: 1.12 95%CI (0.82, 1.53) hospital volume was also not associated with asphyxia or moderate or severe neonatal hypoxic-ischemic encephalopathy. Conclusions: This study observed similar rates of asphyxia and moderate or severe neonatal hypoxic-ischemic encephalopathy for rural and urban hospitals in Alberta and no association with hospital volume.